Fish Oil–Containing Lipid Emulsions in Adult Parenteral Nutrition: A Review of the Evidence. Issue 4 (19th December 2017) - Abbasoglu, Osman; Hardy, Gil; Manzanares, William; Pontes‐Arruda, Alessandro
Abstract: Background . There is evidence from laboratory and animal studies that fish oil–containing intravenous lipid emulsions (FOC‐IVLEs) have a beneficial effect on inflammation and the immune response, suggesting a possible clinical benefit. Clinical studies of FOC‐IVLEs have reported mixed results. The aim of this review is to present findings from recent randomized controlled clinical trials and other quality clinical studies investigating the effects of administering intravenous fish oil alone or as part of a multilipid emulsion and to examine the quality of these studies in an objective, evidence‐based manner. Methods . Studies comparing FOC‐IVLEs with other IVLEs in adults were included. Thirty‐four clinical studies were evaluated: 19 investigated levels of inflammatory and immune markers as an endpoint; 13 investigated rates of infection or sepsis; 3 investigated clinical outcomes in septic patients; and 29 investigated general clinical outcomes. Results . There was conflicting evidence for a beneficial effect of fish oil on levels of inflammatory and immune markers and some evidence that fish oil decreased the rate of postoperative atrial fibrillation. Studies generally reported few statistical differences in clinical outcomes and rates of infection and sepsis with FOC‐IVLEs as compared with other IVLEs. The quality of reporting was generally poor, and the presented evidence for comparisons between FOC‐IVLEs and other IVLEs was inconclusive or weak. Conclusions . There is very little high‐quality evidence that FOC‐IVLEs have a more beneficial effect than other IVLEs on clinical outcomes in adult patients.